Geïntegreerde bediening in die opbou van 'n identiteitsgedrewe missionale gemeente - Nel, Malan (University of Pretoria, 2018)
The role that integration and coordination of ministries play in the discovery and development of a missional congregation’s identity is being investigated in this study. The theory of the building up of a congregation is being investigated after which the identity and missional being of a congregation is subjected to scrutiny. It is being argued that the missional congregation identity is a gift from the triune God. This identity is corporative, relational and dynamic and is initiated by God. The challenge for congregations in a post-Christianity world lies in the fact to anew reclaim and deepen their missional identity. As a result of the research conducted for this study, it is assumed that the intentional integration and coordination of the ministries facilitate the discovery and development of the identity. In this study Nel’s argument that ministries need each other to facilitate the discovery and development of identity is tested. There is synergy between the different ministries in a systems approach and the effectiveness of the ministries is much greater than it would be if they were to function on their own. The various ministries need each other to fully come into their own. Osmer’s four tasks of practical theology were implemented in this study. The empirical research (quantitative as well qualitative) was conducted among the ministers of the Highveld Synod of the Dutch Reformed Church. One-hundred-and-thirty-nine of the 144 ministers agreed to take part in the quantitative research followed by partly structured interviews with 16 randomly selected ministers. During the empirical study every attempt was made to obtain data in connection with the understanding of ministers regarding the building up, identity and missional being of a congregation as well as the integration and coordination of the ministries that are present in their congregations. The probability exists that an identity-driven missional congregation in which the ministry is integrated and coordinated, could go from strength to strength in the world. The research has shown that some of the ministers seem to show a flawed understanding that identity is a relational reality. At the same time there exists quite possibly a defective understanding that a congregation’s reason for existence originates in its identity, and that the contributions that the integration and coordination of the ministry play in the discovery and development of the identity, are not fully understood. Most of the ministers are aware of the fact, that they need to develop their congregations as missional congregations, but the ministers do not always have the knowledge, competence, inclination and experience to make the move. An endeavor is made to better understand these core concerns and in the last chapter strategic plans, with an eye on desired outcomes, are presented.